Risk of aquaculture-derived microplastics in aquaculture areas: An overlooked issue or a non-issue? - Lin, Lin; Chen, Ciara Chun; Zhu, Xiaoshan; Pan, Ke; Xu, Xiangrong (Frontiers in Marine Science, 2022)
Plastic equipment such as fishing nets and foam buoys has been widely used in aquaculture. This kind of equipment would gradually decompose while being subject to the long-term effects of physical, chemical, and biological degradation processes, leading to the release of large amounts of microplastics (MPs) into the local marine environment and the generation of aquaculture-derived MPs (AD-MPs). The rapid growth of aquaculture has resulted in an explosion of AD-MPs with various environmental consequences. The accumulation of MPs in aquatic products was found closely related to the abundance of environmental MPs, suggesting the importance of determining whether AD-MPs increase the risk of MP ingestion by aquatic products and thus endanger aquatic food safety. In this short communication, the ecological and health risks of AD-MPs were discussed and perspectives were proposed for future studies.